ALGEBRAIC STRUCTURES IN HEREDITY HUMAN BLOOD GROUP SYSTEM - Wasil, Moh.; Hartiansyah, Fiqih Rahman; Alifia, Istianah (Journal of Fundamental Mathematics and Applications (JFMA), 2024)
Marriage or in this case the researcher calls it "cross-operation" between two individuals (male and female) who have the same or different blood type has the probability to produce children (offspring) with the same blood type as one of the parents or even have a completely different blood type with both of them, whether it is the ABO blood type system or MN if it is associated with the rhesus system or not. The cross-operation between two individuals can be viewed from a mathematical perspective as an algebraic structure with one closed binary operation (OB). The cross-operation of ABO blood group system is an algebraic structure in groupoid form. The cross-operation of MN blood group system is an algebraic structure in groupoid form. And finally, the cross-operation of ABO and MN blood group systems when associated with the rhesus blood group system is an algebraic structure in groupoid form.